Resolvin D1 Reduces the Immunoinflammatory Response of the Rat Eye following Uveitis - Rossi Settimio; Di Filippo Clara; Ferraraccio Franca; Simonelli Francesca; D'Amico Michele (Mediators of Inflammation)
This study investigated whether the administration of resolvin D1 to rats with endotoxininduced uveitis (EIU) ameliorates the immuno-inflammatory profile of the eye. 24 h after the administration of 200 μg LPS into the footpad of Sprague-Dawley rats, severe changes of the structure of the eye occurred concomitantly with a severe inflammatory and immune response. These latter included strong infiltration of PMN leukocytes CD11b+ T-lymphocytes CD4+ and CD8+ within the eye and a significant release of the cytokines/chemokines TNF-alpha, CXCL8, and RANTES too. Bolus of resolvin D1 (RvD1; 10–100–1000 ng/kg in 200 μL of sterile saline via the tail vein) significantly and dose-dependently (i) reduced the development of the ocular derangement caused by LPS; (ii) reduced the clinical score attributed to EIU; (iii) reduced the protein concentration and myeloperoxidase activity (MPO) in aqueous humor (AqH); and (iv) reduced neutrophils, T-lymphocytes, and cytokines within the eye.